How can we measure sustainability? - Nagy Tamás (REGIONAL AND BUSINESS STUDIES, 2011)
HOW CAN WE MEASURE THE SUSTAINABILITY? Nagy Tamás West-Hungarian University, Faculty of Economics István Széchenyi Management and Organisation Sciences Doctoral School The science has a lot of developed indicators to measure and monitor economic, social phenomena and processes and environmental conditions, but we want now to measure sustainability. The first step is to make an exact definition of the sustainability. The definition made by the Brundtland Commission has two bases: the duality of needs and limitations. For this reason the growth of human needs can only be achieved with harmonic development. The harmonic development is based upon three grounds: on the social forms, on the economical level and on the carrying capacity of natural systems. Therefore, the economical efficiency determines the social reasonableness, and these are limited by the carrying capacity of natural systems. To reach this goal, I analyzed the mainstream of the science in this regard. The Canadian National Round Table on the Environment and the Economy made six sustainability indicators. A US company called Sustainable Measures defined ten measurable interaction factors of the sustainable development. The Global Report Initiative uses triple bottom lines in the assessment. In my dissertation, I survey and compare these methods, and make proposals for usable routines for the European companies.